Photoexcited toluidine blue inhibits tau aggregation in Alzheimer's disease - Dubey, Tushar; Nalini, Gorantla Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The aggregates of microtubule-associated protein Tau are considered as a major hallmark of Alzheimer's disease. Tau aggregates accumulate intracellularly leading to neuronal toxicity. Numerous approaches have been targeted against Tau protein aggregation, which include application of synthetic and natural compounds. Toluidine blue is a basic dye of phenothiazine family, which on irradiation with a 630 nm light gets converted into a photoexcited form, leading to generation of singlet oxygen species. Methylene blue is the parent compound of toluidine blue, which has been reported to be potent against tauopathy. In the present work, we studied the potency of toluidine blue and photoexcited toluidine blue against Tau aggregation. Biochemical and biophysical analyses using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, ThS fluorescence, circular dichroism spectroscopy, and electron microscopy suggested that toluidine blue inhibited the aggregation of Tau in vitro. The photoexcited toluidine blue potentially dissolved the matured Tau fibrils, which indicated the disaggregation property of toluidine blue. The cell biology studies including the cytotoxicity assay and reactive oxygen species (ROS) production assay suggested toluidine blue to be a biocompatible dye as it reduced ROS levels and cell death. The photoexcited toluidine blue modulates the cytoskeleton network in cells, which was supported by immunofluorescence studies of neuronal cells. The studies in a UAS Tau E14 transgenic Drosophila model suggested that photoexcited toluidine blue was potent to restore the survival and memory deficits of Drosophila. The overall finding of our studies suggested toluidine blue to be a potent molecule in rescuing the Tau-mediated pathology by inhibiting its aggregation, reducing the cell death, and modulating the tubulin levels and behavioral characteristics of Drosophila. Thus, toluidine blue can be addressed as a potent molecule against Alzheimer's disease.

Neem derivatives inhibits tau aggregation - Nalini, Gorantla Vijay; Das, Rashmi; Mulani, Fayaj Alam; Thulasiram, Hirekodathakallu V.; Chinnathambi, Subashchandrabose (Journal of Alzheimer s Disease Reports, 2021)
Tau is a phosphoprotein with natively unfolded conformation that functions to stabilize microtubules in axons. Alzheimer's disease pathology triggers several modifications in tau, which causes it to lose its affinity towards microtubule, thus, leading to microtubule disassembly and loss of axonal integrity. This elicit accumulation of tau as paired helical filaments is followed by stable neurofibrillary tangles formation. A large number of small molecules have been isolated from Azadirachta indica with varied medicinal applications. The intermediate and final limonoids, nimbin and salannin respectively, isolated from Azadirachta indica, were screened against tau aggregation. ThS and ANS fluorescence assay showed the role of intermediate and final limonoids in preventing heparin induced cross-β sheet formation and also decreased hydrophobicity, which are characteristic nature of tau aggregation. Transmission electron microscopy studies revealed that limonoids restricted the aggregation of tau to fibrils; in turn, limonoids led to the formation of short and fragile aggregates. Both the limonoids were non-toxic to HEK293T cells thus, substantiating limonoids as a potential lead in overcoming Alzheimer's disease.